Influence of environmental conditions on properties of ionomeric and resin sealant materials - Kamila Rosamilia Kantovitz; Fernanda Miori Pascon; Gisele Maria Correr; Roberta Caroline Bruschi Alonso; Lidiany Karla Azevedo Rodrigues; Marcelo Correa Alves; Regina Maria Puppin-Rontani (University of São Paulo, 2009)
OBJECTIVES: The aim of this study was to determine the effect of environmental conditions on the degradation of ionomeric and resin sealant materials. MATERIAL AND METHODS: FluroShield, Vitremer, and Ketac Molar disc-shaped specimens (n=18/material) were prepared, polished, subjected to initial hardness and roughness readings. Six discs of each material were randomly assigned to one of three different storage solutions: 0.3% citric acid (CA), demineralization solution (DE), and remineralization solution (RE). The specimens were individually immersed in 3 mL of the test solutions, which were daily changed. After 15 days of storage, new surface roughness and hardness readings were done. Fluoride release in the solutions was measured within 15 days. Data were analyzed by ANOVA and Tukey's and Contrast tests (α=0.05). RESULTS: The storage in CA increased the roughness of Vitremer and Ketac Molar. A significant reduction in hardness was observed for all materials after storage in all solutions. For all materials, the greatest amounts of fluoride release occurred during the 1st day. FluroShield presented the same patterns of fluoride release in all solutions. Ketac Molar and Vitremer released the highest amounts of fluoride in the CA solution. CONCLUSIONS: Ionomeric materials are more susceptible to degradation than resin-based materials under acidic conditions. Acidic conditions lead to a higher fluoride release from ionomeric materials.